Application of Hi-throat/Hi-volume SPE technique in analyzing occurrence, influencing factors and human health risk of organophosphate esters (OPEs) in drinking water of China. (1st August 2021) - Zhang, Shengwei; Li, Yanxia; Yang, Chao; Meng, Xiang-Zhou; Zheng, Hongyuan; Gao, Yuan; Cai, Minghong
Abstract: Organophosphate esters (OPEs) are typical industrial additives widely applied in various industrial and household products, but they may pollute drinking water. In the present study, the occurrence of OPEs in drinking water was analyzed. For this purpose, 25 drinking water samples were collected from households in 25 cities in China. The concentrations of OPEs were accurately determined according to a high-throughput organic analysis testing combined with high-volume solid phase extraction (Hi-throat/Hi-volume SPE) technique. Through this technique, nine OPEs were detected, with spiked recoveries from 77% to 101%, and their total concentrations (ΣOPEs) ranging from 46.8 to 251 (average 126) ng L −1 . The detection frequencies of the selected OPEs determined via Hi-throat/Hi-volume SPE were 88.0%–100%, which are much higher than those previously reported. The limit of detections of the OPEs was low at < 0.01 ng L −1, which could be mainly attributed to the high volume of accumulated drinking water (>20 L). OPEs in drinking water presented a decreasing trend from cities in coastal provinces to inland cities of China. Redundancy analysis showed that the concentrations of OPEs in drinking water were significantly influenced by economic–demographic influencing factors. The non-carcinogenic and lifetime carcinogenic risks (non-CR and CR) of the analyzed OPEs in drinking water were negligible for urban residents in China. Graphical abstract: Image 1 Highlights: Ten organophosphate esters in drinking water of China were analyzed. Tris(1-chloro-2-propyl)phosphate was the predominant OPE in drinking water. Organophosphate esters in drinking water were related to anthropocentric activities. Health risks of organophosphate esters in drinking water of China were negligible.